Body Mass Index and Risk for Mental Stress-Induced Ischemia in Coronary Artery Disease - Robert Soufer; Antonio B Fernandez; Judith Meadows; Dorothea Collins; Matthew M Burg (BMC, 2016)
Abstract Acute emotionally reactive mental stress (MS) can provoke prognostically relevant deficits in cardiac function and myocardial perfusion, and chronic inflammation increases risk for this ischemic phenomenon. We have described parasympathetic withdrawal and generation of inflammatory factors in MS. Adiposity is also associated with elevated markers of chronic inflammation. High body mass index (BMI) is frequently used as a surrogate for assessment of excess adiposity and associated with traditional coronary artery disease (CAD) risk factors and CAD mortality. BMI is also associated with autonomic dysregulation and adipose tissue-derived proinflammatory cytokines, which are also attendant to emotion-provoked myocardial ischemia. Thus, we sought to determine if BMI contributes to risk of developing myocardial ischemia provoked by MS. We performed a prospective interventional study in a cohort of 161 patients with stable CAD. They completed an assessment of myocardial blood flow with single-photon emission computed tomography simultaneously during two conditions: laboratory MS and at rest. Multivariate logistic regression determined the independent contribution of BMI to the occurrence of MS-induced ischemia. Mean age was 65.6 ± 9.0 years, 87.0% had a history of hypertension and 28.6% had diabetes. Mean BMI was 30.4 ± 4.7. Prevalence of MS ischemia was 39.8%. BMI was an independent predictor of MS ischemia, odds ratio (OR) = 1.10, 95% confidence interval (CI) [1.01-1.18] for 1-point increase in BMI and OR = 1.53, 95% CI [1.06-2.21] for a 4.7-point increase in BMI (one standard deviation beyond the cohort BMI mean), p = 0.025 for all. These data suggest that BMI may serve as an independent risk marker for MS ischemia. The factors attendant with greater BMI, which include autonomic dysregulation and inflammation, may represent pathways by which high BMI contributes to this risk and serves as a conceptual construct to replicate these findings in larger CAD populations.